Problems of training specialists in the field of information security - I. I. Livshits (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The problem of training specialists in the field of information security seems relevant given the lack of specialists capable of countering new threats. Objectively, there is a significant shortage of qualified specialists who could be trained by technical universities of the Russian Federation in the very near future. When solving this problem, it is important to take into account the level of quality of the graduates and the negative risk from the distance learning mode.Method. The presented work proposes an analysis of the needs for qualified specialists in the program 10.04.01 “Information Security” and a statistical analysis of the final qualifying works of masters of the Faculty of FBIT of ITMO University based on the results of the work of state examination commissions in 2023.Result. An analysis of the needs for qualified information security specialists was carried out based on available data; It is shown that given the current dynamics, it is not possible in the near future to provide the required number of qualified specialists without significant changes in universities. An analysis of the graduate work of masters studying under the 10.04.01 “Information Security” program was carried out in the aspect of the problem posed: examples of excellent performance of work for the “industry” and the risks of performing standard “template” work were reflected.Conclusion. The results can be used to assess the quality of training of specialists in the field of information security in technical universities in Russia.